Yapay zeka tabanlı sosyal medya reklamlarının wom etkisi ve marka sadakati üzerindeki rolü - Mohammad Khodaverdizadeh Gharabaghi (My University, 2025)
Yapay zeka tabanlı sosyal medya reklamlarının wom etkisi ve marka sadakati üzerindeki rolü Bu araştırma, yapay zekâ (AI) tabanlı sosyal medya reklamlarının tüketici davranışı üzerindeki etkilerini incelemekte ve özellikle AI reklam algısının Ağızdan Ağıza İletişim (WOM) ile Marka Sadakati üzerindeki rolünü ortaya koymayı amaçlamaktadır. Çalışmanın temel sorunsalı, sosyal medya gibi yüksek etkileşimli dijital ortamlarda kişiselleştirilmiş AI reklamlarının tüketicilerin paylaşım eğilimlerini ve marka ile uzun vadeli ilişkilerini nasıl şekillendirdiğini anlamaktır. Araştırma nicel ve açıklayıcı (explanatory) desende tasarlanmış, Türkiye’de sosyal medyayı aktif kullanan bireylerden çevrim içi anket yöntemiyle N=233 geçerli veri elde edilmiştir. Ölçümler 5’li Likert tipi ölçeklerle yapılmış; WOM dört maddeden, marka sadakati beş maddeden, AI reklam algısı ise tek maddeden oluşmuştur. Analiz sürecinde güvenirlik testleri (Cronbach’s α), KMO ve Bartlett faktörlenebilirlik ölçümleri, Pearson korelasyonları, standartlaştırılmış tek-yordayıcılı OLS regresyonları, PCA ile boyut indirgeme, K-Means ile kümeleme ve CART karar ağacı analizleri uygulanmıştır. Elde edilen bulgular, AI reklam algısının hem WOM’u ( β=0.463, p

The role of artificial intelligence-based social media ads on wom effect and brand loyalty This study investigates the effects of artificial intelligence (AI)-based social media advertising on consumer behavior, with a specific focus on how AI-driven advertising perception influences Word-of-Mouth (WOM) and Brand Loyalty. The core aim is to understand how personalized AI advertisements shape consumers’ sharing tendencies and their long-term relationships with brands within highly interactive digital environments. The research employs a quantitative and explanatory design, collecting N = 233 valid responses from active social media users in Türkiye through an online survey. Constructs were measured using 5-point Likert scales: WOM (four items), brand loyalty (five items), and AI advertising perception (single item). The analytical process included reliability tests (Cronbach’s α), KMO and Bartlett measures of factorability, Pearson correlations, standardized single-predictor OLS regressions, PCA for dimensionality reduction, K-Means clustering, and CART decision tree analysis. Findings reveal that AI advertising perception has a significant and positive effect on both WOM (β = 0.463, p < .001) and brand loyalty (β = 0.574, p < .001). Additionally, WOM exerts an independent and strong effect on loyalty (β = 0.543, p < .001). K-Means analysis identified two distinct consumer segments: “high engagement–high loyalty” and “low engagement–low loyalty.” CART results further demonstrate that one WOM item and AI perception are the strongest predictors of brand loyalty. This study is considered to provide an original contribution to the literature by testing the relationship between WOM and brand loyalty within the context of AI-based social media advertising through video advertisements and within the same model. In addition, it offers actionable strategic recommendations for marketing professionals through segment-based insights and explanatory decision rules.
The role of artificial intelligence-based social media ads on wom effect and brand loyalty
Keywords: Advertising; Ağızdan ağıza iletişim (WOM); Artificial intelligence; Brand loyalty; Communication; Digital marketing; Digitalization; Dijital pazarlama; Dijitalleşme; İletişim; Kişiselleştirme; Marka sadakati; Personalization; Reklamcılık; Social media; Social media advertising; Sosyal medya; Sosyal medya reklamcılığı; Word-of-mouth (WOM); Yapay zeka; Yapay zekâ